Ziconotide: A rapid detoxification protocol for the conversion from intrathecal morphine–The Raffaeli Detoxification Model - Raffaeli, MD, William; Righetti, MD, Donatella; Sarti, PhD, Donatella; Balestri, MD, Marco; Ferioli, MD, Isabella; Monterubbianesi, MD, Maria Cristina; Caminiti, MD, Alessandro (Journal of Opioid Management, 2018)
Objectives: To assess the efficacy and the safety of our rapid detoxification protocol in preventing signs and symptoms of withdrawal and pain severity. Design: Prospective, open-label case series study. Settings: Public primary care at the Pain and Palliative Care Unit of the Infermi Hospital of Rimini, Italy. Patients: The authors studied 10 consecutive patients suffering from chronic noncancer pain who were refractory to intrathecal (IT) morphine, and hence indicated for ziconotide therapy. Interventions: IT pump was refilled with saline solution, and each patient received endovenous morphine, oral clonidine, ketoprofen, and lorazepam for the first 3 days, and slow-release tramadol, oral clonidine, and ketoprofen for 10 days. Ziconotide therapy was started at the end of the 2-week detoxification treatment. Main outcome measures: The observer-rated opioid withdrawal scale (OOWS) was used for the assessment of withdrawal signs, visual analogue scale was used for pain intensity assessment, and also adverse events were recorded. Results: Withdrawal symptoms were experienced by 3 patients (30 percent). Their average OOWS decreased significantly (p < 0.05) from 4.3 ± 2.5 to 1.7 ± 0.6 at days 3 and 14 of protocol, respectively, with no increment of pain intensity. Withdrawal symptoms were resolved in 4 days on average without the need of adjuvant medications. One patient with high morphine dosage (20 mg/d), interestingly, did not show any withdrawal symptoms. Conclusions: The detoxification protocol was effective in preventing withdrawal signs without increasing pain severity, allowing to rapidly convert IT morphine to ziconotide monotherapy in patients who are refractory to morphine.